(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Six standard beams described in the TRS-457 (IAEA): RQR 5, 8, M1, M2, M3, M4 were simulated using the EGSnrc Monte Carlo code. Each spectrum was created by an X-ray tube simulated in BEAMnrc, and attenuation curves were obtained using the application egs_kerma. The quality of each beam was evaluated by the 1st and 2nd half-value layers, the homogeneity coefficients and the mean energies. All beams presented quality parameters compatible with those described in TRS-457 (IAEA).